Analisis Nilai-Nilai Pendidikan Agama Islam dalam Film Buya Hamka - Siti Tanik Ngaisatul Firdaus; M. Achid Nurseha (IAINU Kebumen, 2026)
Along with the development of technology and media, film does not only function as entertainment but also serves as an educational medium that can convey positive values to society. The film Buya Hamka Vol. 1 is a biographical film that presents exemplary behavior of an Islamic scholar in daily life. Therefore, the purpose of this study is to identify the values of Islamic education in the film Buya Hamka Vol. 1 as viewed from the concepts of tarbiyah, ta'lim, and ta'dib, as well as Islamic educational values which include akidah (faith), ibadah (worship), and akhlaq (morality). This research employed a descriptive qualitative approach with data collection techniques through observation and documentation methods. Meanwhile, the data analysis technique used was content analysis. Based on the results of the study, it can be concluded that the film Buya Hamka Vol. 1 contains Islamic educational values in the form of tarbiyah (guidance), ta'lim (teaching), and ta'dib (character and moral formation), which are reflected in the values of aqidah, ibadah, and akhlaq, such as patience, responsibility, honesty, trust in Allah (tawakkul), and the habit of worshiping Allah Swt. in daily life